(untitled) (International Journal of Automation and Smart Technology, 2025)
Modern electrical devices all strive for improved efficiency, reduced maintenance and reduced carbon emissions. Brushless DC (BLDC) motors represent the most recent development in a long evolution of motor technology. BLDCs provide enhanced reliability, decreased noise and extended lifetime while also providing efficiency superior to that available from AC induction motors. A speed control scheme of a BLDC motor using a Hall effect sensor is proposed. The Pulse Width Modulation (PWM) technique is used for control through a pre-programmed microcontroller, and the motor speed is handled by a remote and displayed in an LCD by the Hall effect sensor. The Hall effect sensor included in the speed control is a good alternative which can improve drive robustness due to reduced cleaning and maintenance. This development is expected to improve remote monitoring and operation of BLDC motors in a single package well-suited for dusty/ limited access environments.